Biodiesel unsaturation degree effects on diesel engine NOx emissions and cotton wick flame temperature - Mohd Fareez Edzuan, Abdullah; Sim Shu, Zhing; Clarence Bilong, Bugik (EDP Sciences, 2016)
As compared with conventional diesel fuel, biodiesel has better lubricity and lower particulate matter (PM) emissions however nitrogen oxides (NOx) emissions generally increase in biodiesel-fuelled diesel engine. Strict regulation on NOx emissions is being implemented in current Euro 6 standard and it is expected to be tighter in next standard, thus increase of NOx cannot be accepted. In this study, biodiesel unsaturation degree effects on NOx emissions are investigated. Canola, palm and coconut oils are selected as the feedstock based on their unsaturation degree. Biodiesel blends of B20 were used to fuel a single cylinder diesel engine and exhaust emissions were sampled directly at exhaust tailpipe with a flue gas analyser. Biodiesel flame temperature was measured from a cotton wick burned in simple atmospheric conditions using a thermocouple. Fourier transform infrared (FTIR) spectrometer was also used to identify the functional groups presence in the biodiesel blends. Oxygen content in biodiesel may promote complete combustion as the NOx emissions and flame temperatures were increased while the carbon monoxide (CO) emissions were decreased for all biodiesel blends. It is interesting to note that the NOx emissions and flame temperatures were directly proportional with biodiesel unsaturation degree. It might be suggested that apart from excess oxygen and free radical formation, higher NOx emissions can also be caused by the elevated flame temperatures due to the presence of double bonds in unsaturated biodiesel.